Distribution Pattern of Refugia and Horticultural Plants in Three Areas of Pamekasan Regency - mohammad Imam sufiyanto; Mohammad Hefni; Aflahah Aflahah; R. Agoes Kamaroellah (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2021)
This study aims to determine the types of refugia and horticulture plants in the Pakong, Pegantenan, Pasean areas in Pamekasan Regency, as well as the factors that influence the diversity of these barrier and horticultural plants. This research is descriptive in nature: Direct observations in three areas in Pamekasan Regency with the roaming method or exploring the area of the area. Descriptive qualitative analysis data found that barrier plant species were found in one class, namely: Dicotyledonae and order three, namely: Malvales, Fabaceae, Pedialiaceae, while for horticultural plants there were two classes namely Monocotyledone and dicotyledone and five orders namely Malvales, Arecaceae, Oleaceae, Sapindaceae, and Malphigiales. Abiotic factors in three areas, namely: Average temperature 6,5, air temperature around 31,7o C, humidity with an average range of 7.4% and the light intensity ranges from an average of 1120lux.